The influence of population movement and acceptance of malaria control programme on malaria occurrence in Tawau, Sabah , 1997 - Asits Sanna; Noor Hidayah Ishak (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Malaria is an infectious disease that remains to be the main health problems in Tawau, Sabah. A case control study was carried out in the district with the aim of determining the influence of population movement and acceptance of malaria control programme on malaria occurrence. Respondents consisted of 142 cases who were randomly selected from the reported cases in 1996 were matched with 142 controls from the same villages by age and sex. Chi square test and t test were used in univariate analysis to determine the association between malaria and the risk factor being studied. The results of univariate analysis showed that malaria occurrence was significantly associated with hearing about malaria from radio, knowledge of malaria symptoms, knowledge of how malaria can be prevented, number of places being visited, movement to jungle, use of preventive measures during movement, having fever after movement and frequency of using treated bednets. Meanwhile the mean score of overall knowledge, attitudes and perceptions between cases and controls showed no significant difference. Further analysis by multiple logistic regression however found that number of places being visited (OR 3.41, CI 95% 1.43- 8.09), use of preventive measures during movement (OR 5.08, CI 95% 1.59 -16.20), hearing about malaria from radio (OR 2.87, CI95% 1.24- 6.67), movement to jungle (OR 3.25, CI 95% 1.25- 8.48) and knowledge of how malaria can be prevented (OR 5.57, CI 95% 1.41 -21.97) were the only factors that were able to predict and influence the occurrence of malaria in Tawau, Sabah.